2019
DOI: 10.3390/w12010071
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological/Hydraulic Modeling-Based Thresholding of Multi SAR Remote Sensing Data for Flood Monitoring in Regions of the Vietnamese Lower Mekong River Basin

Abstract: Synthetic Aperture Radar (SAR) remote sensing data can be used as an effective alternative to detect surface water and provide useful information regarding operational flood monitoring, in particular for the improvement of rapid flood assessments. However, this application frequently requires standard and simple, yet robust, algorithms. Although thresholding approaches meet these requirements, limitations such as data inequality over large spatial regions and challenges in estimating optimal threshold values r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…If various RADAR sensors with different sensor specifics are implemented, then more fluvial traits can be investigated and the weaknesses of the sensors can offset each other. Hong Quang et al [199] used hydrological/hydraulic modeling-based thresholding of multi SAR RS sensors (Sentinel-1) to monitor floods in regions of Vietnam's Lower Mekong River Basin. Alsdorf et al [200] used InSAR technologies to measure water level changes on the Amazon floodplain.…”
Section: Flood Events and Floodplain Risksmentioning
confidence: 99%
“…If various RADAR sensors with different sensor specifics are implemented, then more fluvial traits can be investigated and the weaknesses of the sensors can offset each other. Hong Quang et al [199] used hydrological/hydraulic modeling-based thresholding of multi SAR RS sensors (Sentinel-1) to monitor floods in regions of Vietnam's Lower Mekong River Basin. Alsdorf et al [200] used InSAR technologies to measure water level changes on the Amazon floodplain.…”
Section: Flood Events and Floodplain Risksmentioning
confidence: 99%
“…The district is home to 220,000 people (2019 statistics), who live in an area of 474 km 2 . The average rainfall range varies from 1170 to 1520 mm, and 90-95% of the total annual rainfall is concentrated in the rainy season (May to November) (Quang et al, 2019). The typical crop is rice, which is divided into 2-(no irrigation) or 3-season rice (with irrigation and not flooded in the flooding season).…”
Section: Tam Nong Districtmentioning
confidence: 99%
“…An optimal thresholding algorithm called Hammock Swing Thresholding (HST) was developed, which was applied in Quang et al (2019) for both Sentinel-1 and AlOS-2 images because it has shown its high accuracy and consistency with different SAR inputs. The concept of HST is simple: it minimizes the total absolute values of the difference layer between the SAR and reference water extent in order to obtain an optimal Vegetation type S1 AL2 S1 Scatters AL2 Scatters…”
Section: Thresholdingmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing-based flood-detection methods can be divided into two categories: optical and radar sensor. Optical data such as WorldView2 [4], Landsat [5][6][7], Spot-5 [8], sentinel [9], Moderate-Resolution Imaging Spectroradiometer (MODIS) [7,10] and RADAR [8,[11][12][13] had been explored for flood detection. In the meanwhile, machine-learning algorithms including decision tree algorithm [4,14], SVM [6,8], MLP [8] had been developed for flood detection.…”
Section: Introductionmentioning
confidence: 99%